Utilizing PUNITA experiments to evaluate fundamental delayed gamma-ray spectroscopy interrogation requirements for nuclear safeguards. Issue 8 (2nd August 2020) - Rodriguez, Douglas Chase; Koizumi, Mitsuo; Rossi, Fabiana; Seya, Michio; Takahashi, Tohn; Bogucarska, Tatjana; Crochemore, Jean-Michel; Pedersen, Bent; Takamine, Jun
ABSTRACT: Present safeguards verification methods for small samples of high-radioactivity nuclear material (e.g. spent nuclear fuel solution) in reprocessing facilities use destructive analysis techniques since passive non-destructive techniques are incapable of directly determining the nuclear material content. To supplement these methods, the Japan Atomic Energy Agency and European Commission Joint Research Centre (JRC) are collaborating to develop delayed gamma-ray spectroscopy non-destructive assay technology for composition analysis of the fission nuclides. Multiple experiments were performed in the JRC-Ispra site using the Pulsed Neutron Interrogation Test Assembly (PUNITA) to study the signature from short-lived fission products from low-radioactivity U and Pu standard samples. From these spectra, we identify many gamma rays useful to determine the composition of a mixed nuclear material sample. Here we present the results of these experiments along with correlations to the interrogation, mass, volume, and sample homogeneity.